Electron Impact Ionization of Ground-State Be-Like Rare Gas Ions (Journal of Atomic and Molecular Sciences, 2012)
Detailed calculations for electron impact ionization including direct ionization (DI) and excitation autoionization (EA) processes along the ground-state Be-like rare gas ions have been performed by using relativistic distorted wave (RDW) approximation. The DI contribution from $2s$ shell and the EA contributions from inner-shell electron impact excitations of $1s-nl$ $(n≤ 12, l ≤ 4)$ were considered. The contribution of DI is a little more than 90% to the total electron impact ionization cross section. The main EA contribution comes from $1s-2p$ electron impact excitation channel. The EA contribution relative to DI contribution first increased and then decreased as the atomic number $Z$ increases in Be-like rare gas ion. The EA rate coefficients are given for all ground-state Be-like rare gas ions as a function of impact electron temperature.
Keywords: electron impact ionization; excitation autoionization (EA); relativistic distorted wave (RDW) approximation.